The Effect of Using Low‑Phytate Cereal Varieties on Phosphorus Digestibility and Selected Production Indices - Ondřej Malý; Jan Mareš; Iveta Zugárková; Lukáš Mareš (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2017)
The pollution of surface waters by excessive biogenic elements, especially phosphorus, is a highly topical subject. Fishery management on ponds may be one of the potential sources of phosphorus in waters. Cyprinid fish generally have a very poor digestion of the phosphorus contained in the plant‑based components of feeds. In them, phosphorus is deposited in the form of phytic acid which is almost indigestible for cyprinids. The conducted testing was focused on affecting the digestibility of phosphorus contained in plant‑based feeds. Two of the cereals most frequently grown in the Czech Republic were tested, namely, wheat and barley. Control feeds were varieties commonly grown in our country, i.e. Vánek and Bojos. Furthermore, we used special cereal mutant lines with a decreased content of the phytic acid, JS‑12/IDO 563 and M955. The test results showed that when using the low‑phytate wheat line, the digestibility of phosphorus was increased by up to 11.21 % (P < 0.01); and by 5.89 % (P < 0.05) in the case of barley. Both low‑phytate lines of the cereals used significantly affect phosphorus digestibility and decrease the loading of the environment with phosphorus. When using the low‑phytate wheat line, a significant effect (P < 0.05) was found on the fat content in the fish body compared to the control variety but also compared to the low‑phytate barley line. No significant effect was found comparing both control varieties and comparing the barley varieties mutually.